Comparison of Oblique And Orthogonal Planes of Temperomandibular Joint in Magnetic Resonance Scan - V Sanjay; K S Ganapathy; M Priscilla David (Wolters Kluwer Medknow Publications, 2003)
MRI is the most recent imaging modality since 1984 that has been shown to posess a good capability for diagnosing the Tempero Mandibular Joint disc, its derangement and other structural changes of the joint. MRI is unique since there is no associated radiologic risk. The purpose and aim of this study is to determine whether it is possible to improve image quality by setting the scanning plane in oblique sagittal and coronal instead of in the orthogonal planes and to identify the position of the discs in symptomatic and asymptomaticTMJ. MRI was performed on symptomatic and asymptomatic individuals using B'lscint 0.5 tesla MRI machine. Pairs of oblique and orthogonal images were obtained and evaluated. Finding of this study showed superior image quality in oblique scanning planes of TMJ compare to orthogonal planes. Conclusion of this study showed improved diagnostic quality of the images of TMJ obtained in oblique scanning planes.